Well-applied local governance in an urban area - Ridho Al-Hamdi (Masyarakat, Kebudayaan dan Politik, 2020)
This paper analyses the application of local governance in addressing education and health affairs in contemporary Indonesia. There are three main objectives: explaining the development of local governance, finding out the impact of the local governance on public services, and investigating driving factors that influence the local governance application. Methodologically, it is qualitative research by employing a case study. Therefore, the Yogyakarta municipality was selected as the study object due to its outstanding achievements, such as the city cleanest of corruption (2009-2010), the most livable city in Indonesia (2010-2011), and the top rank of the Indonesian governance index (2014). In-depth interviews of eight informants and documentary methods are utilized as data-gathering techniques. The study’s finding is threefold; first, the development of the municipal government can be divided into three steps: the phase of installation of democratic systems, the phase of plentiful signs of progress, and the stable situation. Second, the impact of the governance process on education and health issues is increasing the municipal budget from year to year, supporting facilities, integrated systems, and the pro-poor people policy. Third, a fourfold determining factor that can influence the successful governance: the city mayor’s leadership, a good partnership and cooperation amongst governance actors, the availability of well-educated civil servants, and the maximization of local-owned resources.